2021
DOI: 10.48550/arxiv.2110.11633
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Explainable Landscape-Aware Optimization Performance Prediction

Abstract: Efficient solving of an unseen optimization problem is related to appropriate selection of an optimization algorithm and its hyper-parameters. For this purpose, automated algorithm performance prediction should be performed that in most commonly-applied practices involves training a supervised ML algorithm using a set of problem landscape features. However, the main issue of training such models is their limited explainability since they only provide information about the joint impact of the set of landscape f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In addition, it has been shown that personalizing the regression models to the problem instance that is being solved can decrease the predictive error [2]. Furthermore, a recent study provides global (across all benchmark problem instances) and local (for a single problem instance) explanations of which ELA features are most important when a supervised ML algorithm is used to predict an optimization algorithm performance [22]. However, these explanations have not been analyzed when different supervised ML methods are used in the predictive task.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, it has been shown that personalizing the regression models to the problem instance that is being solved can decrease the predictive error [2]. Furthermore, a recent study provides global (across all benchmark problem instances) and local (for a single problem instance) explanations of which ELA features are most important when a supervised ML algorithm is used to predict an optimization algorithm performance [22]. However, these explanations have not been analyzed when different supervised ML methods are used in the predictive task.…”
Section: Related Workmentioning
confidence: 99%